Countenance Evaluation of Virtual Reality (VR) Implementation in Machining Technology Courses - Waskito Waskito; Rizky Ema Wulansari; Budi Syahri; Nelvi Erizon; Purwantono Purwantono; Yufrizal Yufrizal; Tze Kiong Tee (Journal of Applied Engineering and Technological Science (JAETS), 2023)
This study aims to evaluate whether virtual reality (VR) learning media can be used in Machining Technology courses which are practical learning but implemented virtually. The research using the Stake Countenance evaluation method was carried out at the Department of Mechanical Engineering FT-UNP in the July-December 2021 semester with 60 students as research subjects. This study was mix method by using sequential explanatory design. which is the collection of quantitative and qualitative data that is carried out sequentially. Data related to the antecedents, transaction, and outcomes phases were collected using questionnaires, interviews, and observations. The research begins with developing VR media that is implemented to learning materials in the field of Machining Technology and then applied to learning. Then first stage is carried out using quantitative then the next stage or the second stage is carried out using qualitative. The result of research showed that this VR application can help students understand the theory of introducing machine tool operations but have not been able to run machine. This study imply that students’ learning process should be enjoyable and also influence existing practices of Student-Centered Learning. The novelty of this study showed the evaluation result of technology, especially virtual reality can be implemented in the practice learning course, it can be reference for educator to consider implementing technology in practice learning. This study will contribute to existing knowledge and various instructional method that can be implemented by educator